Automatização de uma máquina de vazão de líquidos - Gouveia, André Antonio (2012)
The regulation and automatic control of industrial systems represent an essential matter on science development and engineering. Nowadays globalization and the strong competition had risen the importance of automation for the modernization of industrial processes. Vending machines, or yet self-services, have reached more and more space on global market throughout the years, by developing easy using practices. The present final graduation project reports the automation of a liquid flow machine, showing all the electronic and mechanic components inserted in a beer cooler, for the liquid to be served automatically. It presents elements of microcontrollers programming with liquid flow monitoring and controlling, acting in a water pump. It also brings the electric circuits layouts and the source code implemented on the AT89S52 microcontroller. Besides the explanation of how the automation is done, the present work also exposes the theoretical approach to the functioning of the used equipment.